PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIKA DITINJAU DARI MULTIPLE INTELLIGENCES SISWA - Kamid Kamid; Evita Anggereini; Muhtadin Muhtadin (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
This study aimed to determine the activities of teachers and students as well as conceptual understanding of students in terms of multiple intelligences of students by using classroom action research which was conducted in three cycles and each cycle carried out in two meetings. Data collection methods are observation, questionnaire, and tests in each cycle. Based on the results of research activities of teachers and students showed an increase from cycle to cycle. With the results in the first cycle is 57.29%, the second cycle is 73.44%, and the third cycle is 79.43% while the activity of students in the first cycle is 56.51%, the second cycle is 71.09% and the third cycle is 78.13%. Conceptual understanding of students in each intelligence also increased, namely: (1) Interpersonal intelligence and mathematical intelligence in cycle I was 90%, cycle II was 97.92%, and cycle III was 98.21%. (2) Interpersonal intelligence and intra-personal intelligence in cycle I was 56.33%, cycle II was 75.83%, and cycle III was 82.86%. (3) Intra personal intelligence and musical intelligence in cycle I is 70%, cycle II is 83.33%, and cycle III is 87.50%. (4) Interpersonal intelligence and body movement intelligence in cycle I is 50%, cycle II is 62.5%, and cycle III is 71.43%. (5) Intra personal intelligence and linguistic intelligence in cycle I is 60%, cycle II is 70.83%, and cyce III is 78.57%. and (6) Naturalist intelligence and intelligence body movements in cycle I were 85%, cycle II was 87.5%, and cycle III was 92.86%